Acceptance, prevalence and indications for robot-assisted laparoscopy: results of a survey among urologists in Germany, Austria and Switzerland - Imkamp, Florian; Rassweiler, Jens (Urologia internationalis, 2015)
Background: Robotic-assisted laparoscopy (RAL) is being widely accepted in the field of urology as a replacement for conventional laparoscopy (CL). Nevertheless, the process of its integration in clinical routines has been rather spontaneous. Objective: To determine the prevalence of robotic systems (RS) in urological clinics in Germany, Austria and Switzerland, the acceptance of RAL among urologists as a replacement for CL and its current use for 25 different urological indications. Materials and Methods: To elucidate the practice patterns of RAL, a survey at hospitals in Germany, Austria and Switzerland was conducted. All surgically active urology departments in Germany (303), Austria (37) and Switzerland (84) received a questionnaire with questions related to the one-year period prior to the survey. Results The response rate was 63%. Among the participants, 43% were universities, 45% were tertiary care centres, and 8% were secondary care hospitals. A total of 60 RS (Germany 35, Austria 8, Switzerland 17) were available, and the majority (68%) were operated under public ownership. The perception of RAL and the anticipated superiority of RAL significantly differed between robotic and non-robotic surgeons. For only two urologic indications were more than 50% of the procedures performed using RAL: pyeloplasty (58%) and transperitoneal radical prostatectomy (75%). On average, 35% of robotic surgeons and only 14% of non-robotic surgeons anticipated RAL superiority in some of the 25 indications. Conclusions: This survey provides a detailed insight into RAL implementation in Germany, Austria and Switzerland. RAL is currently limited to a few urological indications with a small number of high-volume robotic centres. These results might suggest that a saturation of clinics using RS has been achieved but that the existing robotic capacities are being utilized ineffectively. The possible reasons for this finding are discussed, and certain strategies to solve these problems are offered.
Gesehen am 22.11.2018